Little Red Cap - Kinkead, Evalyn; Grimm, Jacob 1785-1863.; Grimm, Wilhelm 1786-1859.; Probst, E. (St. Louis Webster, 1965)
A little girl meets a hungry wolf in the forest while on her way to visit her sick grandmother.
Adapted from Grimm's fairy tales.
Keywords: Fairy tales; Folklore -- Germany